Elucidation of mechanisms underlying TGF-β-driven downregulation of HSF2 in breast cancer progression - Eskelinen, Katriina (My University, 2026)
Metastasis is the leading cause of cancer-related mortality, and its initiation requires cancer cells to acquire invasive traits. A central mechanism enabling this switch is epithelial-to-mesenchymal transition (EMT), a morphological program that cancer cells can hijack. Recent findings show that transforming growth factor-β (TGF-β) suppresses heat shock factor 2 (HSF2) transcription in breast cancer cells concomitantly with EMT, yet the regulatory mechanism underlying this repression remains unknown. This thesis aimed to verify that TGF-β-mediated HSF2 suppression is transcriptional, and to identify the specific HSF2 promoter regions and transcription factors (TFs) mediating this downregulation. To distinguish transcriptional repression from enhanced mRNA decay, HS578T human breast cancer cells were treated with the transcription inhibitor actinomycin D with or without TGF-β, followed by qRT-PCR-based mRNA stability measurements. To pinpoint the HSF2 promoter area mediating TGF-β-induced HSF2 repression, truncated HSF2 promoter fragments were cloned into luciferase reporters and transfected into HS578T cells, followed by luciferase reporter assays. A DNA affinity purification (DAP) protocol was established and optimized to isolate TGF-β-responsive TFs using biotinylated promoter probes incubated with nuclear extracts from ± TGF-β-treated HS578T cells, followed by streptavidin-based capture. The results revealed that TGF-β does not promote mRNA degradation, indicating that downregulation occurs at the transcriptional level. Reporter assays identified a 0.5-kb region immediately upstream of the 5’ untranslated region as the principal HSF2 promoter segment mediating TGF-β-responsive HSF2 downregulation. The piloted DAP, however, lacked sufficient specificity for mass spectrometry, indicating that further methodological optimization is required before TF identification can proceed. In conclusion, this thesis demonstrates that TGF-β suppresses HSF2 transcriptionally and identifies the proximal 0.5-kb promoter region as the key regulatory element mediating this repression. These findings provide a foundation for identifying the TGF-β-responsive TFs acting on the 0.5-kb promoter region and for understanding how TGF-β-driven transcriptional regulation contributes to invasive behavior during breast cancer progression.
Keywords: breast cancer, cancer invasion, cellular plasticity, epithelial-to-mesenchymal transition, heat shock factor 2, transforming growth factor-β